Fiscal consolidation programs and income inequality - Brinca, Pedro (2017)
Pedro Brinca is grateful for financial support from the Portuguese Science and Technology Foundation, grants number SFRH/BPD/99758/2014, UID/ECO/00124/2013 and UID/ECO/00145/2013. Miguel H. Ferreira is grateful for financial support from the Portuguese Science and Technology Foundation, grant number SFRH/BD/116360/2016. Hans A. Holter is grateful for financial support from the Research Council of Norway, Grant number 219616; the Oslo Fiscal Studies Program.